PENETAPAN KADAR FENOLIK TOTAL FRAKSI POLR DAN NONPOLAR DAUN RAMBAI LAUT (Sonneratia caseolaris L.) DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Jubaidah, Siti; Sundu, Reksi; Sabriningsih, Nur (Jurnal Riset Kefarmasian Indonesia, 2019)
Rambai laut (Soneratia caseolaris L.) is a type of tree that grows in riverbank swamps or mangrove forests which contains one of the secondary metabolites in the form of phenolic compounds. The purpose of this study was to determine the total phenolic content of polar and nonpolar fractions of sea rambai leaves using UV-Vis spectrophotometry method. Research conducted is non-experimental. The stages of the study included the determination of plants, sampling, making samples, making extracts, determining the water content of extracts, fractionation using polar and nonpolar fractions, phytochemical screening test of ethanol extract and fractionation results and determination of total phenolic levels by UV-Vis spectrophotometry. The results showed that rambai laut leaf in polar fraction had a total phenolic content of 213.49 ± 1.2227 mg GAE / g, which means that in each gram the polar fraction is equivalent to 213.49 mg of gallic acid, whereas in the nonpolar fraction of rambai laut leaves is obtained 55.79 ± 1.0809 mg GAE / g which means that in each gram the nonpolar fraction is equivalent to 55.79 mg of gallic acid. Total phenolic content is greater in the polar fraction.